2014
DOI: 10.1155/2014/371419
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Tong‐Sai‐Mai Decoction against Apoptosis Induced by H2O2 in PC12 Cells: Mechanisms via Bcl‐2‐Mitochondria‐ROS‐INOS Pathway

Abstract: Tong-Sai-Mai decoction (TSM) is a Chinese materia medica polyherbal formulation that has been applied in treating brain ischemia for hundreds of years. Because it could repress the oxidative stress in in vivo studies, now we focus on the in vitro studies to investigate the mechanism by targeting the oxidative stress dependent signaling. The relation between the neurogenesis and the reactive oxygen species (ROS) production remains largely unexamined. PC12 cells are excitable cell types widely used as in vitro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…A previous study reported that ROS was associated with apoptosis of cells ( 39 ). In the present study, Caco-2 cells incubated for 6 and 12 h in the presence of hyperoxia and at higher doses of H 2 O 2 exhibited a significantly increased number of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that ROS was associated with apoptosis of cells ( 39 ). In the present study, Caco-2 cells incubated for 6 and 12 h in the presence of hyperoxia and at higher doses of H 2 O 2 exhibited a significantly increased number of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that that abnormal apoptosis of neuronal cells is one of the causes of ND 31) . The key to controlling apoptosis is that mitochondria release pro-apoptotic proteins after being stimulated by DNA damage, ROS, and other stress signals, triggering a series of apoptosis pathways 32) . In this study, we found significant changes in MMP of HT22 cells induced by glutamate, which is consistent with the results of other cell models 33,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, excess ROS was detected, which is associated with apoptosis, as ROS promotes mitochondrial toxicity and macromolecular membrane damage, and consequently DNA fragmentation 19 34 35 . Thus, it is evident, that the excess ROS in mitochondria contribute to the mitochondrial caspase apoptotic signalling pathway 19 36 37 . Hence, we concluded that HY-PDT induces apoptosis by facilitating ROS production.…”
Section: Discussionmentioning
confidence: 99%